EXPERIENCE IN SURGICAL TREATMENT OF DIAPHYSICAL FRACTURES OF THE SHIN BONES - Eranov Sherzod Nuraliyevich (European Science Publishing, 2025)
The results of blocked intramedullary osteosynthesis (BIOS) in 50 patients with fractures of the distal and diaphysis of the tibia are presented. Blocked intramedullary osteosynthesis is a reliable and predictable method for the treatment of diaphyseal fractures of the tibia, which allows the restoration of limb function in the shortest possible time in most patients.
Keywords: Blocking intramedullary osteosynthesis, tibia, implant.